2017
DOI: 10.1080/00365513.2017.1292538
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reactivity in thromboelastometry. Revision of the FIBTEM test: a basic study

Abstract: This study aimed to investigate modifications to the FIBTEM test to better assess fibrinogen levels and the quality of fibrin polymerization in citrated blood using Multiplate impedance aggregometry to verify platelet inhibition. Blood samples from 26 healthy volunteers were subjected to thromboelastometry studies (EXTEM/FIBTEM tests) in accordance with the standard study protocol (cytochalasin D) and according to a modified protocol (synthetic IIbIIIa receptor antagonist vs. acetylsalicylic acid [ASA] + synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, in addition to platelet counts, multiple dynamic test systems have been developed to rapidly identify these patients including the critical administration threshold (CAT), the assessment of blood consumption (ABC) score, and other dynamic platelet function tests (diamond of death) as identified by thrombelastography (TEG). These tests have been recommended in various studies (7,(113)(114)(115)(116)(117)(118), while other studies found no evidence for benefit using TEG and ROTEM (119).…”
Section: Management Of Coagulopathymentioning
confidence: 99%
“…Therefore, in addition to platelet counts, multiple dynamic test systems have been developed to rapidly identify these patients including the critical administration threshold (CAT), the assessment of blood consumption (ABC) score, and other dynamic platelet function tests (diamond of death) as identified by thrombelastography (TEG). These tests have been recommended in various studies (7,(113)(114)(115)(116)(117)(118), while other studies found no evidence for benefit using TEG and ROTEM (119).…”
Section: Management Of Coagulopathymentioning
confidence: 99%
“…[11,12] FIBTEM is one of the ROTEM parameters and provides information about the change of fibrinolytic system, including fibrinogen concentration and fibrin polymerization. [13] In recent years, a number of articles have reported the usefulness of ROTEM as a POC device in numerous clinical situations such as emergency care, cardiovascular surgery, liver transplantation, trauma surgery, and septic disseminated intravascular coagulation. [11,1417] FIBTEM is reported as an effective early predictor for massive bleeding and transfusion in orthopedic hip surgery and trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Other in vitro studies have demonstrated that "platelet noise" remains in the FIBTEM assay despite the addition of CytD. 3,4 This indicates that the MCF FIBTEM overestimates the "fibrinogen effect" on the clot strength because of both an undefined effect of the reagent on the plasmatic coagulation system and an incomplete inhibition of the platelet effect on the clot. However, this effect can be minimized by translating "dual platelet" inhibition from clinical into laboratory practice.…”
mentioning
confidence: 98%